The Regional Migration-Development Nexus in Australia: What Migration? Whose Development? - Boese, Martina; Moran, Anthony (Frontiers in Sociology, 2021)
Both regional resettlement of refugees, and the attraction of different kinds of migrant labour to regional areas, have been significant trends in Australia’s recent migration policies. Using the concept of the migration-development nexus, we address important questions about the nature and scope of development these different policies aim to promote, and achieve. We examine the intersection of policies and initiatives implemented to encourage and support refugee settlement and regional migration in Australia with the perspectives of regionally settled migrants and refugees on their regional migration outcomes. We argue that recent government policies, and multi-stakeholder initiatives aimed at regional migration and/ or settlement, cast migrants as differential contributors to regional development, useful either in terms of their skills (skilled migrants) or their labour (backpackers, seasonal workers, refugees). The co-presence of different groups of migrants in regional locations is also shaped by the fluctuating employer demands for mobile labour in combination with visa regulations. We draw on data from three projects on regional settlement, multiculturalism and mobilities to analyse three important elements of regional migration that are central to a critical analysis of the nexus between rural migration and development in regional Australia: the complex roles of employers; the embedding of regional migration in migrants’ life courses; and the tension between long-term migration outcomes and quick fixes. By focusing on development as it is experienced by migrants themselves and interpreted by different stakeholders in regional migration, we draw attention to the limitations of a purely instrumental view of migrants as agents of regional development. We argue that the sustainability of regional migration policies will depend on recognizing the important role of migrants’ hopes, needs and aspirations as well as their rights, and the unintended human costs and consequences of exclusively economically driven migration policy design.skilled